مطالعہ سیرت اور غیر اسلامی مآخذومصادر - ڈاکٹرحافظ محمدعبدالقیوم (FIKR-O NAZAR فکر ونظر, 2012)
In orientalist tradition the study of Sirah is an academic subject not a religious one. The orientalists utilize non-religious sources in this study including social sciences and other disciplines. By the same taken, non-Muslim religious traditions, particularly the Judeo-Christian tradition are also amongst their major sources. With the passage of time, Muslim Sirah writers have also accommodated this trend in their studies. This paper attempts to understand and explore this trend by analyzing the academic worth of these sources and their significance in this discipline. It also shows how this approach has widened the scope of Sirah study and created a space to explore the life of the Holy Prophet ﷺ as a historic personality who has its ever lasting imprints on human civilization and religious tradition.